Police and crime control in Jamaica : problems of reforming ex-colonial constabularies - Harriott, Anthony (UWI Press MonaJM, 2000)
Analyzes the changes in the social organization of crime in Jamaica. Provides an overview of the structural features of the police force. Examines the major problems facing the Jamaica Constabulary Force viz. corruption, its style of work and relations with the citizenry.